Stochastic Dominance of CTA Funds - Hooi, Hooi Lean (Institutional Knowledge at Singapore Management University, 2013)
In this paper, we employ the stochastic dominance (SD) approach to rank the performance of commodity trading advisors (CTA) funds. An advantage of this approach is that it alleviates the problems that can arise if CTA returns are not normally distributed by utilizing the entire returns distribution. We find both first-order and higher-order SD relationships amongst the CTA funds and conclude that investors are better off investing in the first-order dominant funds to maximize their expected utilities and expected wealth. However, for higher-order dominant CTAs, risk-averse investors can maximize their expected utilities but not their expected wealth. In addition to the advantages of the SD approach in the case of non-normal returns, the paper concludes that the approach is more appropriate compared with traditional approaches as a filter in the CTA selection process as it provides meaningful economic interpretation of the results.